Superconductivity in mercurides of strontium - Nixon, Rachel; Prots, Yurii; Krnel, Mitja; Zaremba, Nazar; Pavlosiuk, Orest; Schmidt, Marcus; Akselrud, Lev; Grin, Yuri; Svanidze, Eteri (Frontiers in Materials, 2024)
A large variety of chemical and physical properties are exhibited by mercurides and amalgams. In this work, we have successfully examined seven strontium mercurides: SrHg11, SrHg8, Sr10Hg55, SrHg2, SrHg, Sr3Hg2, and Sr3Hg. The interest in the mercury-rich region is motivated by the large number of mercury-based superconductors that have high mercury content. At the same time, the preparation on the mercury-rich side of the binary phase diagram is experimentally non-trivial, due to the high vapor pressure of mercury and extreme air-sensitivity of mercury-rich compounds. By employing a set of specialized techniques, we were able to discover superconductivity in three mercury-strontium compounds – SrHg11 (Tc=3.2±0.3 K, Hc2=0.18±0.05 T), SrHg8 (Tc=3.0±0.1 K, Hc2=0.35±0.02 T), and Sr10Hg55 (Tc=2.2±0.25 K, Hc2=0.54±0.05 T).